Quality Measurement and Improvement Study of Surgical Coronary Revascularization: Medication Adherence (MISSION-2) - Liu, Chong-Yang (Chin Med J (Engl), 2018)
BACKGROUND: Secondary preventive therapies play a key role in the prevention of adverse outcomes after coronary artery bypass grafting (CABG). However, medication adherence after CABG is often poor, and conventional interventions for improving adherence have limited success. With increasing penetration of smartphones, health-related smartphone applications might provide an opportunity to improve adherence. Carefully designed trials are needed to provide reliable evidence for the use of these applications in patients after CABG. METHODS: The Measurement and Improvement Studies of Surgical Coronary Revascularization: Medication Adherence (MISSION-2) study is a multicenter randomized controlled trial, aiming to randomize 1000 CABG patients to the intervention or control groups in a 1:1 ratio. We developed the multifaceted, patient-centered, smartphone-based Heart Health Application to encourage medication adherence in the intervention group through a health self-management program initiated during hospital admission for CABG. The application integrated daily scheduled reminders to take the discharge medications, cardiac educational materials, a dynamic dashboard to review cardiovascular risk factors and secondary prevention targets, and weekly questionnaires with interactive feedback. The primary outcome was secondary preventive medication adherence measured by the Chinese version of the 8-item Morisky Medication Adherence Scale at 6 months after randomization. Secondary outcomes included all-cause death, cardiovascular rehospitalization, and a composite of death, myocardial infarction, stroke, and repeat revascularization. DISCUSSION: Findings will not only provide evidence regarding the feasibility and effectiveness of the described intervention for improving adherence to CABG secondary preventive therapies but also explore a model for outpatient health self-management that could be translated to various chronic diseases and widely disseminated across resource-limited settings. TRIAL REGISTRATION: https://clinicaltrials.gov(NCT02432469).